ZAUFANIE A POLITYKA. ZAŁOŻENIA TEORETYCZNE - Schwan, Gesine (Wydział Prawa i Administracji UAM, 2007)
Few notions have enjoyed such prosperity in recent years as the word trust. Empirical examples of the importance of trust for the success of democracy, or successful market economy can be even found in newspapers. This demand for trust today is also the best prove o f its short supply. At the same time, however, there is a danger o f a soon saturation as it is becoming increasingly difficult to listen to that word being repeated again and again. In order redress this situation, perhaps we should resign for some time from quoting everyday debates and use the historical development o f the idea to present the historical long term relationship between trust and free cohabitation as well as the basic meaning of that relation. Undoubtedly, systematic deliberations on the political and philosophical meaning of trust are needed i f one wishes to find the foundations o f today’s debate in the history o f the idea. From today’s point o f view, sociologically, and from the point o f view of the historically developing and changing attitudes, one might ask about the actual chances o f trust in Germany, Europe, and globally.
POLITICS AND TRUST. THEORETICAL ASSUMPTIONS